The Impact of Nutrition on the Prevention of Complications (Encephalopathy, Ascites) in Patients with Liver Cirrhosis : A Systematic Review of Randomized Controlled Trials and Primary Studies - Nabilla Ladyan Finasisca; Ryandri Yovanda (The Indonesian Journal of General Medicine, 2026)
Introduction: Liver cirrhosis (LC) is an advanced stage of hepatic fibrosis with estimated annual mortality exceeding 1.3 million deaths globally. Hepatic encephalopathy (HE) and ascites represent the most clinically consequential complications, dramatically impairing patients' quality of life and substantially increasing mortality risk. Malnutrition, present in 20–80% of cirrhotic patients, has been increasingly recognized as both a consequence and a determinant of these complications. Nutritional interventions—including branched-chain amino acid (BCAA) supplementation, zinc repletion, protein optimization, late evening snacks (LES), and probiotic administration—may constitute modifiable strategies for complication prevention. This systematic review aimed to comprehensively evaluate the impact of nutritional interventions on the prevention of HE and ascites in patients with LC. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligible studies included randomized controlled trials (RCTs), cohort studies, case-control studies, cross-sectional studies, and observational studies involving adult patients (≥18 years) with diagnosed liver cirrhosis, reporting nutritional interventions and outcomes related to HE, ascites, or associated biomarkers. Risk of bias was assessed using the Cochrane RoB 2.0 tool for RCTs and the Newcastle-Ottawa Scale (NOS) for observational studies. Results: Twenty-three primary studies (15 RCTs and 8 observational studies) encompassing 8,214 patients were included. Nutritional therapy significantly reversed minimal hepatic encephalopathy (MHE) in 71.1% of treated patients versus 22.8% controls (P=0.001). BCAA supplementation improved event-free survival (HR 0.67; 95%CI 0.49–0.93; P=0.015). Probiotics reduced overt HE development (HR 2.1 for controls versus probiotic group; P<0.05). Late evening snacking improved total body protein stores significantly over 12 months (P=0.003). Zinc supplementation reduced serum ammonia and improved Child-Pugh scores (P=0.01 and P=0.04, respectively). L-ornithine L-aspartate (LOLA) combined with standard therapy reduced 28-day mortality (16.4% versus 41.8%; P=0.001). Zinc deficiency independently predicted new or worsening ascites (HR 2.8; 95%CI 1.6–14.1; P=0.021). Discussion: The evidence synthesized confirms that targeted nutritional interventions meaningfully modulate the pathophysiological pathways underlying HE and ascites in LC. Multiple mechanisms are implicated: BCAA supplementation restores Fischer's ratio and reduces hyperammonemia; zinc repletion corrects metalloenzyme deficiencies essential for urea-cycle function; probiotics reduce gut-derived ammonia production and bacterial translocation; LES mitigates accelerated starvation metabolism; and adequate protein intake prevents sarcopenia. Sodium restriction with concurrent adequate caloric intake remains a cornerstone for ascites management, although poor adherence represents a clinically significant challenge. Conclusion: Multi-modal nutritional interventions—encompassing protein optimization (1.2–1.5 g/kg/day), BCAA supplementation, zinc repletion, probiotic administration, LES, and individualized caloric delivery—exert clinically significant protective effects against HE and ascites in patients with LC. Integration of formal nutritional assessment and individualized clinical nutrition strategies into multidisciplinary cirrhosis management pathways is strongly recommended. Further large-scale, multicenter RCTs with standardized nutritional protocols are needed to establish definitive guidelines.